1982
DOI: 10.1111/j.1365-2494.1982.tb01600.x
|View full text |Cite
|
Sign up to set email alerts
|

Leaf surface expansion on the main axes of white and red clovers

Abstract: Plants of white clover (Trifolium repens L.) cv. Blanca and red clover (7". pratense L.) cv. Hungaropoly were grown singly in controlled environments. The effects of eight treatments on the two species were examined: 16-and 8-h photoperiods x 20/15 and 15/IO''C day/night temperalures X Rhizobium-hee plants receiving nitrate N and inoculated plants receiving no combined N. Twice weekly measurements ofthe main axis leaf size, petiole length, rate of leaf production and the time period between the appearance of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1988
1988
2002
2002

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…The difference in mean RGR between the two species was much greater at 8~ than at 10 or 12~ Other authors have also reported that clover shows a greater increase in growth rate than ryegrass at spring temperatures (Arnott and Ryle, 1982;Davidson et al, 1986;Mitchell and Lucanus, 1960). However, although all plants were supplied with non-limiting mineral N, the actual DM yields of the ryegrass seedlings were several times greater than the clover seedlings, even at the higher temperatures.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The difference in mean RGR between the two species was much greater at 8~ than at 10 or 12~ Other authors have also reported that clover shows a greater increase in growth rate than ryegrass at spring temperatures (Arnott and Ryle, 1982;Davidson et al, 1986;Mitchell and Lucanus, 1960). However, although all plants were supplied with non-limiting mineral N, the actual DM yields of the ryegrass seedlings were several times greater than the clover seedlings, even at the higher temperatures.…”
Section: Discussionmentioning
confidence: 81%
“…1983L Other authors have also concluded that nitrogenase activity does not limit growth more at spring temperatures than at higher temperatures, in another white clover cultivar (Blanca) (Woledge and Calleja Suarez, 1983), and a number of tropical and temperate legumes (Gibson, 1965;1974). However, other reports are contradictory (Arnott and Ryle, 1982;Mytton and Hughes, 1980). The latter authors did not nodulate plants before the commencement of the temperature treatments, thus in these experiments the effects of temperature on N2 reduction were confounded with those on infection and nodule formation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Leaf growth is also influenced by the source from which white clover plants obtain their N. Plants receiving N from the soil have a greater leaf area than those which depend on rhizobially fixed N (Ryle et al 1979;Arnott & Ryle 1982). Again, this may be a direct result of C partitioning.…”
Section: Introductionmentioning
confidence: 99%
“…However, the application of N fertiliser to mixed swards can decrease the proportion of white clover (Laidlaw et al 1992), particularly in spring following a late winter N application (Laidlaw 1985;Rowarth et al 1996). This is because low temperatures decrease the growth rate of white clover more than ryegrass, and hence white clover is less responsive to N than ryegrass (Arnott & Ryle 1982;Davidson et al 1986). However, the physiological limiting factor in white clover growth has not yet been identified.…”
Section: Introductionmentioning
confidence: 99%